Integrated Operating Room: A Systematic Mapping Review - Arenas, Carolina; Garcés, Lina (Journal of Health Informatics, 2021)
Objective: To analyze existing IORs reported in scientific literature, verifying how they are designed and if they really help improve patients’ safety and professionals’ quality of work. Method: We conducted a systematic mapping review. Result: We analyzed 13 primary studies that propose or use software systems of IORs. We found that IORs have contributed to improving surgical procedures in hospitals, especially those related to anesthetists’ work. We also noticed that, despite different implementations, there is little understanding about IORs’ software designs. Conclusion: The engineering of IORs is in its early stage; hence more contributions from scientific and technological communities are required.